The subcellular distribution of palmitoyl coenzyme a synthetase in rat brain - Kerr, Eileen Jean Lorna (My University, 2015)
Unique among natural membranes, myelin has a very high lipid content and in the mature animal, a very slow metabolic turnover rate. Following reports in the literature (Pande and Mead, 1968; Cantrill, B.C., Ph.D. Thesis, 1978) of a putative plasma membrane location for the fatty-acid activating enzyme, palmitcyl coenzyme A synthetase, the possibility arises that this enzyme might, to some extent, be responsible for the reduced fatty acid . metabolism of myelin and oligodendrocyte cytosol.